2006
DOI: 10.1007/s10926-006-9037-0
|View full text |Cite
|
Sign up to set email alerts
|

Keyboard use and musculoskeletal outcomes among computer users

Abstract: Several methodological limitations, including non-representative samples, imprecise or biased measures of exposure and health outcome, incomplete control of confounding, and reversal of cause and effect, may contribute to the heterogeneity of observed results. Suggestions are made for improving the validity of future investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
107
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(112 citation statements)
references
References 48 publications
2
107
0
3
Order By: Relevance
“…MSDs were responsible for 34% of all workplace injuries and illnesses in the year 2012 and reportedly cost between $45 to $54 billion to U.S economy [3,4]. Upper body pains such as neck and shoulder pains are the most typical issues among MSD patients as a result of static posture, working technique and constant static muscle activity [1,[5][6][7][8][9]18]. These problems might be worse for mobile computing product such as tablet and smart phone users because of the inseparable screen and keyboard.…”
Section: Introductionmentioning
confidence: 99%
“…MSDs were responsible for 34% of all workplace injuries and illnesses in the year 2012 and reportedly cost between $45 to $54 billion to U.S economy [3,4]. Upper body pains such as neck and shoulder pains are the most typical issues among MSD patients as a result of static posture, working technique and constant static muscle activity [1,[5][6][7][8][9]18]. These problems might be worse for mobile computing product such as tablet and smart phone users because of the inseparable screen and keyboard.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that similar estimates for the European Union (EU) countries are not available, several crosssectional studies performed in Europe have reported a prevalence of 30-62% of musculoskeletal symptoms in the neck or shoulder region studies, and suggest that referred complaints would increase with age and working age, being more prevalent among women than men [4,[6][7][8][9][10][11][12]. However, as this same difference has been identified in the general working population, its causative association may be doubtful [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Musculoskeletal symptoms are widespread among computer users with a high incidence of symptoms, especially in the neck-shoulder region, and the costs and impact on quality of life due to these symptoms are considerable (1)(2)(3)(4). Occupational computer use has become increasingly common over the past few decades, in particular among office workers; and the widespread use of computers today, together with the high incidence of symptoms, demonstrates a potential for the prevention or alleviation of symptoms among, for example, office workers, through the use of targeted interventions.…”
mentioning
confidence: 99%